The Re-Evaluation of Existing School Buildings in Turkey within the Context of 'Green School' - Cakir, Sagra; Taygun, Gokce Tuna (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2021)
Purpose It is seen that major repairs and refurbishments in existing school buildings in Turkey are mostly intended for structural reinforcement and physical facilities, and the Green School design principles are not considered in the process of the new school designs and refurbishment applications in existing schools. Moreover, the participation of students, teachers and parents in environmental decisions in design process regarding school building and its environment is not ensured sufficiently. The purpose of the research is to determine of the knowledge, views, wishes and tendencies of the students, teachers and parents which are the three main components of the school community related to the general characteristics of the school building and its contribution to environmental education. Design/Methodology/Approach A questionnaire form was used as a tool. The survey was conducted in two secondary schools in Ankara in 2017-2018 academic year. Data were analyzed with SPSS 24.0 with the help of experts. Findings The majority of the participants believe that the open spaces in the schools do not provide enough opportunities for interaction with the natural environment, the green spaces in the schools are not sufficient in terms of quality and quantity, the noise in the classrooms is clearly disturbing, but the artificial lighting, temperature and ventilation were found to be relatively adequate. Research Limitations/Implications When selecting the schools, it was among the schools that are planned to be maintained and repaired in the 2018-2019 academic year by the Ministry of National Education and the schools built after 1990 taking into consideration compliance with today's conditions and the adaptability of technological systems. Originality/Value This research stimulates readers and stakeholders to discuss the environmental education provided to the future decision makers (children) through the school buildings.
Keywords: Environment; environmental education; green schools; green school design criteria; school buildings; DESIGN; Architecture